مرويات حاتم بن حريث الطائي في كتب السنة: جمعا ودراسة - بازمول، أحمد بن عمر بن سالم (جامعة المدينة العالمية, 2022)
عنوان البحث: مرويات حاتم بن حريث الطائي في كتب السنة جمعاً ودراسة، ويهدف البحث: إلى تحرير درجة حاتم بن حريث الطائي في الرواية، مع جمع مروياته، ودراستها. وتكون البحث من: مقدمة، ومقصدين، وخاتمة، والفهارس، فالمقدمة: ذكرت فيها سبب اختيار الموضوع، وأهميته، والخطة، والمنهج. والمقصد الأول: ترجمة حاتم بن حريث الطائي، وأقوال النقاد فيه. والمقصد الثاني: دراسة الأحاديث التي رواها حاتم بن حريث الطائي. ثم الخاتمة: وفيها أبرز النتائج، والتوصيات. الفهارس: وهي فهرس المصادر والمراجع، وفهرس الموضوعات، وتظهر أهمية البحث: أنه متعلق بترجمة راوٍ مختلف فيه لم تسبق دراسته مع جمع مروياته، وخلص الباحث في الخاتمة إلى: أن حاتم بن حريث الطائي صدوق حسن الحديث، بلغ عدد مروياته التي وقفت عليها خمس روايات؛ ثلاثة مرفوعة صريحة، واثنان لهما حكم الرفع، ويوصى الباحث: بجمع أحاديث الرواة الذين لهم ميزة عند المحدثين، وتحقيق ما لم يحقق من كتب السنة والرجال. Research title: Narratives of Hatim bin Harith al-Ta’i in the books of the Sunnah, collection and study. The research consists of: an introduction, two objectives, a conclusion, and indexes, The introduction: I mentioned the reason for choosing the topic, its importance, the plan, and the method. The first purpose: the translation of Hatim bin Harith, Al-Ta’i, and the sayings of critics about it. The second purpose: to study the hadiths narrated by Hatim bin Harith Al-Ta’i. Then the conclusion: which includes the most prominent results, and recommendations. Indexes: It is the index of sources and references, and the index of topics. The importance of the research appears: it is related to the translation of a different narrator in which he had not previously studied with the collection of his narrations, In the conclusion, the researcher concluded: that Hatim bin Harith Al-Ta’i is a good hadeeth, His stories, on which she stood, amounted to five, Three explicitly raised, and two have the rule of lifting. The researcher recommends: collecting the hadiths of the narrators who have an advantage with the modernists, and verifying what has not been achieved from the books of Sunnah and men.
Keywords: الحديث النبوي -- السنة النبوية -- الطائي، حاتم بن حريث، ت. حو. 138 هـ. -- رواة الحديث